Modelling of Organo-Mineral Complexes in the System “Lime-Zeolite-Enzyme” for Purifying Technically Polluted Water from Suspended Solids and Compacting Sediment - Guzii, Sergii; Tovmachenko, Andriy; Viter, Volodymyr (Academic journal Industrial Machine Building Civil Engineering, 2025)
The article presents the results of experimental and statistical modelling to determine the optimal composition of organo-mineral complexes for cleaning technically polluted water from suspended solids and compacting sediment in storage ponds at solid waste landfills during their reclamation and reconstruction. Water transparency with a turbidity index of 1.55 NTU they ensured by using an organo-mineral complex containing 7.25-8.25% quicklime, 2.5-3% zeolite and 7.5-8.25% enzyme. Sedimentation in the form of a sediment with a tensile strength of up to 160 kPa on the 28th day of exposure they ensured by using an organo-mineral complex containing 30.63-35% quicklime, 0-3.5% zeolite and 0-1.25% enzyme.